Euthanasia: would elderly people from socio-economic classes D/E perform it or allow it on their relatives? - Rezende, Diego Fraga; Oliveira, Gabriela Nunes; Vianna, Lucy Gomes; Santos, Izabel Borges dos (Revista Kairós-Gerontologia, 2014)
75 opinions from elderly people of low socioeconomic classes living in a specific community were investigated, about whether they would allow euthanasia to be performed on family members. 77.3% wouldn't perform euthanasia. Regarding permission to a physician, the following responded with negatives: 78.7% against the active form, 68% against the passive, and 62.7% against double effect. The contrary arguments were: religious issues, belief in destiny, hope of healing, don't want to take responsibility and guilty conscience.